2021
DOI: 10.1016/j.heliyon.2021.e06558
|View full text |Cite
|
Sign up to set email alerts
|

The potential of metformin as an antineoplastic in brain tumors: A systematic review

Abstract: Brain tumors are challenging to handle and cause severe mortality and morbidity. The primary therapy for brain tumors, a combination of radiotherapy, chemotherapy (i.e temozolomide), and corticosteroids, is considered inadequate to improve patients' clinical conditions and associated with many adverse effects. There is an urgent need for new compounds or repurposing of existing therapies, which could improve brain tumor patients' prognosis. Metformin, commonly used for type 2 diabetes medication, has been exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Interestingly, the gene signature typically induced by the hypoxic GBM microenvironment was partially modified by metformin in a cell model (49). A recent systematic review showed that the combination of metformin with temozolomide given post-radiotherapy achieved better OS and PFS as compares with temozolomide alone (50). However, a recent pooled analysis produced opposite results (26).…”
Section: Ketogenic Diet In Gbmmentioning
confidence: 99%
“…Interestingly, the gene signature typically induced by the hypoxic GBM microenvironment was partially modified by metformin in a cell model (49). A recent systematic review showed that the combination of metformin with temozolomide given post-radiotherapy achieved better OS and PFS as compares with temozolomide alone (50). However, a recent pooled analysis produced opposite results (26).…”
Section: Ketogenic Diet In Gbmmentioning
confidence: 99%
“…The mechanisms of the potential protective effect of metformin on MBT remain unknown, but some biological effects of metformin can explain such an observation. MBT cells are dependent on glucose metabolism (a phenomenon known as the Warburg effect) and the mammalian target of rapamycin (mTOR) signaling to support their proliferation and growth [18,30]. Metformin inhibits the mitochondrial complex 1 of electron transport and reduces energy supply to cancer cells [12,18].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…MBT cells are dependent on glucose metabolism (a phenomenon known as the Warburg effect) and the mammalian target of rapamycin (mTOR) signaling to support their proliferation and growth [18,30]. Metformin inhibits the mitochondrial complex 1 of electron transport and reduces energy supply to cancer cells [12,18]. Metformin has been shown to inhibit glioblastoma cell growth and induce cell cycle arrest, autophagy, and apoptosis in in vitro studies.…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations